Hereditary breast cancer; Genetic penetrance and current status with BRCA - Mahdavi, Morteza; Nassiri, Mohammadreza; Kooshyar, Mohammad Mahdi; Vakili‐Azghandi, Masoume; Avan, Amir; Sandry, Ryan; Pillai, Suja; Lam, Alfred King‐yin; Gopalan, Vinod (Journal of cellular physiology, 2019)
The most important cause of developing hereditary breast cancer is germline mutations occurring in breast cancer (BCs) susceptibility genes, for example, BRCA1, BRCA2, TP53, CHEK2, PTEN, ATM, and PPM1D. Many BC susceptibility genes can be grouped into two classes, high‐ and low‐penetrance genes, each of which interact with multiple genes and environmental factors. However, the penetrance of genes can also be represented by a spectrum, which ranges between high and low. Two of the most common susceptibility genes are BRCA1 and BRCA2, which perform vital cellular functions for repair of homologous DNA. Loss of heterozygosity accompanied by hereditary mutations in BRCA1 or BRCA2 increases chromosomal instability and the likelihood of cancer, as well as playing a key role in stimulating malignant transformation. With regard to pathological features, familial breast cancers caused by BRCA1 mutations usually differ from those caused by BRCA2 mutations and nonfamilial BCs. It is essential to acquire an understanding of these pathological features along with the genetic history of the patient to offer an individualized treatment. Germline mutations in BRCA1 and BRCA2 genes are the main genetic and inherited factors for breast and ovarian cancer. In fact, these mutations are very important in developing early onset and increasing the risk of familial breast and ovarian cancer and responsible for 90% of hereditary BC cases. Therefore, according to the conducted studies, screening of BRCA1 and BRCA2 genes is recommended as an important marker for early detection of all patients with breast or ovarian cancer risk with family history of the disease. In this review, we summarize the role of hereditary genes, mainly BRCA1 and BRCA2, in BC.